2023
DOI: 10.3390/polym15071612
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Protective Effects of Agaro-Oligosaccharides against Hydrogen Peroxide-Stimulated Oxidative Stress

Abstract: In our previous research, we investigated the anti-inflammatory activity of the agaro-oligosaccharides prepared from the agar of Gracilaria lemaneiformis (AO). In the present study, in order to further explore the bioactivities of AO, the antioxidant activity of AO was investigated in vitro in Vero cells and in vivo in zebrafish. AO scavenged alkyl, 1,1-diphenyl-2-picrylhydrazyl, and hydroxyl radicals at the IC50 value of 4.86 ± 0.13, 3.02 ± 0.44, and 1.33 ± 0.05 mg/mL, respectively. AO significantly suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Therefore, ROS are an indicator of cellular stress and apoptosis [25,26]. Moreover, they are known to be important regulators of autophagy activation, and targeting increased autophagy and ROS production has been identified as a novel therapeutic approach for the treatment of several types of cancer [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ROS are an indicator of cellular stress and apoptosis [25,26]. Moreover, they are known to be important regulators of autophagy activation, and targeting increased autophagy and ROS production has been identified as a novel therapeutic approach for the treatment of several types of cancer [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…All of them concern macroalgae or pure compounds of not-detailed algal origin. Many algal compounds exert their antioxidant effect by increasing the activity of endogenous antioxidant enzymes like SOD, CAT, and GPx [34], decreasing ROS production [35,36], and/or decreasing the expression of iNOS, leading to a decreased production of NO [37]. In skeletal myoblasts, algal compounds (phloroglucinol and Indole-6-carboxaldehyde) exerted antioxidant effects by regulating oxidative stress-induced apoptosis, mainly by decreasing mitochondrial dysfunction and modulating apoptosis-regulatory factors (e.g., caspases, Bcl-2, Bax, and cytochrome c) [38,39].…”
Section: Potential Health Benefits Of Algal Antioxidantsmentioning
confidence: 99%
“…Most in vivo experiments (Table 2) were conducted on zebrafish embryos, a wellestablished model system, including as a preclinical screening model. Results showed that extracts and isolated compounds from Fucus virsoides [35], Gracilaria lemaneiformis [36] (oligosaccharide), Hizikia fusiforme [51] (polysaccharide), Padina boryana [52], Pyropia yezoensis [53] (polyphenol), Sargassum fulvellum [54] (polysaccharide), and Undaria pinnatifida sporophylls [55] (polysaccharide) were successful in decreasing oxidative stress by reducing lipid peroxidation and ROS production, leading to decreased heart-beating disorders and increased survival rates. The liver and kidneys are particularly susceptible to the deleterious effects of ROS/RNS due to their elevated metabolic and mitochondrial activity.…”
Section: Potential Health Benefits Of Algal Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation